2022
DOI: 10.1128/aem.01886-21
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Microbiome Dynamics of Putative Denitrifying Bacteria in Two Octocoral Species Exposed to Dissolved Organic Carbon (DOC) and Warming

Abstract: Mutualistic nutrient cycling in the coral-algae symbiosis depends on limited nitrogen (N) availability for algal symbionts. Denitrifying prokaryotes capable of reducing nitrate or nitrite to dinitrogen could thus support coral holobiont functioning by limiting N availability. Octocorals show some of the highest denitrification rates among reef organisms, however little is known about the community structures of associated denitrifiers and their response to environmental fluctuations. Combining 16S rRNA gene am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 93 publications
1
14
1
Order By: Relevance
“…In numerous host-microbe systems, bacteria aid holobiont health and functioning via structuring of the microbiome [8][9][10], provisioning of (essential) metabolites or nutrients [11][12][13] mitigating stress responses [14,15], or changes in their host's life history [16]. Bacteria in corals are thought to support holobiont functioning via nutrient cycling [17][18][19][20][21][22], antimicrobial activity [23,24], and antioxidant capacity [25].…”
Section: Introductionmentioning
confidence: 99%
“…In numerous host-microbe systems, bacteria aid holobiont health and functioning via structuring of the microbiome [8][9][10], provisioning of (essential) metabolites or nutrients [11][12][13] mitigating stress responses [14,15], or changes in their host's life history [16]. Bacteria in corals are thought to support holobiont functioning via nutrient cycling [17][18][19][20][21][22], antimicrobial activity [23,24], and antioxidant capacity [25].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, our results match with recent studies conducted on the pulsating octocoral X. umbellata which showed no negative responses to individual DOC treatments regardless of their concentrations at the ecophysiological level ( Simancas-Giraldo et al, 2021 ). Soft corals may display higher tolerance to enriched DOC concentration in the water than hard corals, by either up taking the available DOC as an additional source of energy via the host ( Fabricius & Klumpp, 1995 ), or by regulating internal nutrient availability of the holobiont via the role that the host-associated bacterial communities ( e.g ., denitrifying bacteria) might play under changing environments ( Xiang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seawater salinity was kept at 35 ± 0.6 ppt, pH of 8.2 ± 0.1, and temperature at 26.0 ± 0.3 C (mean ± SE) and exposed to a 12:12 light:dark period at constant light intensity (120.8 ± 10.2 µmol m −2 s −1 ), while additional chemical water parameters, such as the pH, KH, Ammonium (NH 4 + ), Nitrite (NO 2 − ), Nitrate (NO 3 − ) and Phosphate contents (PO 4 3− ) were measured and adjusted manually twice per week. A general summary on the chemical parameters through the experiment can be found in Vollstedt et al (2020) while other relevant parameters such as salinity and pH can be found summarized by treatment in Xiang et al (2021) . We additionally present details on the recorded mean values measured per tank through the experiment in our Material S1 .…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations